2015
DOI: 10.1111/imr.12378
|View full text |Cite
|
Sign up to set email alerts
|

Ncf1 polymorphism reveals oxidative regulation of autoimmune chronic inflammation

Abstract: The current review on the function of neutrophil cytosolic factor 1 (NCF1) and induced reactive oxygen species (ROS) is based on a genetic search for the major genes controlling autoimmune inflammatory disorders. Surprisingly, the disease-promoting allele determined a lower ROS response and was therefore in complete contrast to the prevailing dogma. Once cloned, it opened the possibility to dissect this complex field from a new angle and with the possibilities to study the role of ROS in vivo. We found that NC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 149 publications
(192 reference statements)
1
114
1
Order By: Relevance
“…For example, Ncf1 congenic studies have revealed an unexpected, protective role of ROS in autoimmunity. Such findings contrast with the prevailing view of the role of ROS in inflammatory diseases, and have since been confirmed in both mice and humans (Holmdahl et al, 2016). With the discovery that many autoimmunity loci associate with multiple autoimmune diseases (Richard-Miceli and Criswell, 2012), including RA (Begovich et al, 2004; Bottini et al, 2004), congenic strains have become a highly useful tool for investigating the contributions of RA-associated genes to other autoimmune diseases.…”
Section: Rat Arthritis Models: Lessons Learned and Limitationscontrasting
confidence: 61%
See 1 more Smart Citation
“…For example, Ncf1 congenic studies have revealed an unexpected, protective role of ROS in autoimmunity. Such findings contrast with the prevailing view of the role of ROS in inflammatory diseases, and have since been confirmed in both mice and humans (Holmdahl et al, 2016). With the discovery that many autoimmunity loci associate with multiple autoimmune diseases (Richard-Miceli and Criswell, 2012), including RA (Begovich et al, 2004; Bottini et al, 2004), congenic strains have become a highly useful tool for investigating the contributions of RA-associated genes to other autoimmune diseases.…”
Section: Rat Arthritis Models: Lessons Learned and Limitationscontrasting
confidence: 61%
“…For example, mutated Ncf1 has been associated with the spontaneous development of lupus (Kelkka et al, 2014) and with increased severity of psoriasis in animal models (Khmaladze et al, 2014) and of gout in the mouse (Schauer et al, 2014). Our current understanding of the role of Ncf1 in autoimmunity has recently been reviewed (Holmdahl et al, 2016). …”
Section: Different Strategies Of Disease Gene Identificationmentioning
confidence: 99%
“…NOX2 supports the function of T regulatory cells and changes the activation threshold of autoreactive T cells; it influences protein phosphatases, protein tyrosine kinases, the linker for activation of T cells (LAT), and tryptophan metabolism/ IDO; regulates the IFN/STAT1 pathway and innate lymphocyte activation; and contributes to regulation of autophagy, although some of these suggested mechanism are controversial (reviewed in ref. 55).…”
Section: Discussionmentioning
confidence: 99%
“…Neutrophil cytosolic factor 1 (an essential component of the NOX 2 complex)-mutated mice lacked formation of NETs when they developed arthritis [33] . The priming step of NACHT, LRR, and PYD domains containing protein 3 (NLRP3) inflammasome expression requires ROS as well [34] .…”
Section: Inflammatory Reaction Stagementioning
confidence: 99%